Selfless ignorance: Too good to be true - Homayoon Moradi (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
We use a range of dictator game experiments to investigate whether people avoid information altruistically. After learning about a product with positive externalities, a consumer may avoid learning the cost of the product so that she does not hesitate to act altruistically. We find that although a few altruistic people avoid information about their own costs, this does not change the overall rate of altruistic behavior. The result suggests that although concealing costs upfront might make a few people let go of learning them, it does not increase the rate of altruistic behavior.
Keywords: C91; D64; D83; D01; 330; Pro-social behavior; Self-Image; Information Avoidance; Moral Wiggle Room